Analysis of The Influence of Shopping Lifestyle, Time Pressure, Religius, and Islamic Financial Literacy on Impulsive Buying on Shopee Live Streaming - Karmila Sari; Saniatun Nurhasanah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Use of live streaming platforms in shop has become trends in the digital era, in particular through Shopee Live Streaming application. This research aims to analyze influence style life shopping, pressure time, religiosity, and literacy Islamic finance towards behavior purchase impulsive on the platform. Research sample taken as many as 100 respondents and processed use Structural Equation Modeling Partial Least Square (SEM-PLS) method with application SmartPLS 3. Stages testing done with the Evaluation of Measurement Model (Outer Model) and Evaluation of Structural Model (Inner Model) tests . The results of this research show that Shopping Lifestyle and Time-Pressure are consistent positive show influence significant influential against impulse buying on Shopee Live Streaming. However , Religiosity and Islamic Financial Literacy have connection negative and not significant regarding Impulse Buying on Shopee Live Streaming. And overall the variables Shopping Lifestyle, Time-Pressure, Religiosity and Islamic Financial Literacy contribute of 46.5% in influence Impulse Buying Variable . Keywords: Shopping Lifestyle, Time-Pressure, Religiosity, Islamic Financial Literacy, Live Streaming, Impulse Buying.